Pathophysiology of NAFLD and NASH in Experimental Models: The Role of Food Intake Regulating Peptides - Kořínková, L.; Pražienková, V.; Černá, L.; Karnošová, A.; Železná, B.; Kuneš, J.; Maletínská, Lenka (Frontiers in Endocrinology, 2020)
Obesity, diabetes, insulin resistance, sedentary lifestyle and Western diet are the key factors underlying non-alcoholic fatty liver disease (NAFLD), one of the most common liver disease in developed countries. In many cases, NAFLD further progresses to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and to hepatocellular carcinoma. Currently, the two-hit theory of NAFLD progression is accepted. The first hit is an imbalance in fatty acid metabolism leading to the accumulation of triglycerides in the liver. The second hit is oxidative metabolic stress and cytokine dysregulation. The mechanisms of NAFLD progression to NASH are still not well understood. In this review, we explore the role of food intake regulating peptides in NAFLD and NASH mouse models. Leptin, an anorexigenic peptide, is involved in hepatic metabolism, and has an effect on NAFLD experimental models. Glucagon-like peptide-1 (GLP-1), another anorexigenic peptide, and GLP-1 receptor agonists (GLP-1R), represent potential therapeutic agents to prevent NAFLD progression to NASH. On the other hand, the deletion of ghrelin, an orexigenic peptide, prevents age-associated hepatic steatosis in mice. Because of the increasing incidence of NAFLD and NASH worldwide, the selection of appropriate animal models is important to clarify aspects of pathogenesis and progression in this field. We also review the key findings describing available mouse models that help better understand disease pathogenesis and progression.